Kepentingan Jepang Menghapus Hutang Luar Negeri Myanmar Tahun 2012-2013 - Neno Elviana; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research analysest Japan’s interest to remove Myanmar foreign debtin 2012 to 2013. Japan has bilateral relationship with Myanmar before WorldWar II. Post independence from colonialism, Myanmar has a military government(military juntas) system. But, Japan continue to provide foreign aid to Myanmar.in 2003 Japan stopped its foreign aid to Myanmar because of Human RightsIssue. This research used relevant concept and theories such as national interestconcept, international cooporation theory, decision making theory, and foreig aidtheory. This Research shows that Japan’s national interest is to remove Myanmarforeign debt for economic and political interest of Japan.Keyword: Nation Interest, Foreign Aid, Japan, Military Juntas.